2011
DOI: 10.2319/021710-99.1
|View full text |Cite
|
Sign up to set email alerts
|

A histochemical study on condylar cartilage and glenoid fossa during mandibular advancement

Abstract: Objective: To evaluate cellular hypertrophic activities in the mandibular condylar cartilage (MCC) and the glenoid fossa (GF) during mandibular advancement in the temporomandibular joint (TMJ) of Sprague-Dawley rats, as evidenced by fibroblast growth factor 8 (FGF8). Methods and Materials: Fifty-five female 24-day-old Sprague-Dawley rats were randomly divided into four experimental and control groups, with a mandibular advancement appliance on the experimental rats' lower incisors. The rats were euthanized on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 28 publications
2
33
0
1
Order By: Relevance
“…Due to the morphological, anatomical, and structural similarities to human condyles and mandibles, the rat model was chosen for this study. [5] The findings of this study with respect to three parameters (A-B, A-D, and B-C) indicate that Group I showed significant mandibular and condylar growth without any external stimulus during T0-T1. This result suggests the role of condylar growth in growing rats.…”
Section: Discussionmentioning
confidence: 55%
“…Due to the morphological, anatomical, and structural similarities to human condyles and mandibles, the rat model was chosen for this study. [5] The findings of this study with respect to three parameters (A-B, A-D, and B-C) indicate that Group I showed significant mandibular and condylar growth without any external stimulus during T0-T1. This result suggests the role of condylar growth in growing rats.…”
Section: Discussionmentioning
confidence: 55%
“…Reportedly, cartilaginous tissue is present in the mandibular fossa or the continuous articular eminence of rats, 46,47 young monkeys. 48 Only a few studies have investigated whether this type of cartilage exists in the mandibular fossa of the human fetus.…”
Section: Discussionmentioning
confidence: 99%
“…43 A further analysis involving Sprague-Dawley rats has highlighted upregulation of fibroblast growth related factor (FGF8) following mandibular advancement over periods ranging from 3 to 30 days. 44 Cellular enlargement and differentiation were observed in both the condylar cartilage and the glenoid fossa during treatment with bony apposition by endochondral ossification in the condyle and intra-membranous ossification in the glenoid fossa.…”
Section: 33mentioning
confidence: 99%